Gender Diversity, Equity, and Inclusion in Academia A Conceptual Framework for Sustainable Transformation - Duarte, Melina; Losleben, Katrin; Fjørtoft, Kjersti (Taylor & Francis, 2023)
Institutional focus on diversity, equity, and inclusion affects all parts of higher education management. Gender Diversity, Equity, and Inclusion in Academia: A Conceptual Framework for Sustainable Transformation scrutinises the conceptual framework for diversity, equity, and inclusion actions in academia to facilitate research-based and critically reflected decisions in higher education management. The book contains 24 chapters, each focused on one of 24 fundamental concepts that are essential for identifying, understanding, and implementing organizational changes and counteracting unjustified disadvantages faced by women and members of other gender minorities in academia, preceded by an introductory binding chapter. The book also discusses concepts directed towards solutions, such as affirmative action and feminist pedagogies, and overcomes the traditional binary approach on gender by incorporating specific challenges faced by LGBTQ+ and transgender staff and students. Gender Diversity, Equity, and Inclusion in Academia will be key reading for academics in Gender Studies and Education Studies, while also serving as a vital resource for individual consumers working in or preparing to enter leadership positions in higher education.